2021
DOI: 10.2147/cmar.s300601
|View full text |Cite
|
Sign up to set email alerts
|

Value of Contrast-Enhanced Ultrasound in the Differential Diagnosis of Focal Splenic Lesions

Abstract: Purpose To identify and validate contrast-enhanced ultrasound (CEUS) features for differentiating malignant from benign splenic lesions. Patients and Methods Splenic lesions in 123 patients who underwent conventional ultrasound (B-mode US) and CEUS were included in this study. Two radiologists evaluated the sonograms of B-mode and CEUS. Statistical analysis was performed to identify significant imaging predictors for splenic malignant lesions. Two other radiologists ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
0
12
1
Order By: Relevance
“…However, 1 of the 22 cases was initially mistaken for a malignant lesion due to its rapid hyper-enhancement in the arterial phase followed by rapid wash-out, and ultimately was proven to be splenic TB by surgical histopathology. This enhancement pattern was inconsistent with the results from a previous study, which demonstrated that splenic TB lesions generally presented persistent enhancement during the intermediate parenchymal phase, and the rapid wash-out pattern was common in malignant splenic lesions but was rare in benign lesions [ 10 , 21 ]. We assumed that this unusual enhancement pattern is be likely associated with the neovascularization and the formation of arterio-venous fistula involved in splenic TB [ 20 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, 1 of the 22 cases was initially mistaken for a malignant lesion due to its rapid hyper-enhancement in the arterial phase followed by rapid wash-out, and ultimately was proven to be splenic TB by surgical histopathology. This enhancement pattern was inconsistent with the results from a previous study, which demonstrated that splenic TB lesions generally presented persistent enhancement during the intermediate parenchymal phase, and the rapid wash-out pattern was common in malignant splenic lesions but was rare in benign lesions [ 10 , 21 ]. We assumed that this unusual enhancement pattern is be likely associated with the neovascularization and the formation of arterio-venous fistula involved in splenic TB [ 20 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Studies demonstrated that CEUS can differentiate between benign and malignant splenic lesions and reported that the benign splenic lesions typically showed iso-enhancement or hyper-enhancement in the arterial phase followed by slow and incomplete wash-out, while malignant lesions initially showed slight hypo-enhancement followed by rapid and complete wash-out [ 10 , 20 ]. The iso-enhancement or hyper-enhancement of benign splenic lesions can reflect their rich vascular structures and enhanced arterial supply.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The display rate of 2D US for splenic tuberculosis is already extremely high. CEUS has little value in improving the display rate of splenic tuberculosis, but it is superior to 2D US in evaluating the internal blood supply to the lesion ( 9 12 ). CEUS of splenic tuberculosis showed that the lesions were mostly non-enhanced ( Figure 4 ) ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…CEUS has been shown to be a particularly valuable tool for splenic analysis, with the ability to determine and monitor alterations in the size, presence, and character of focal lesions, as well as detect specific alterations in its normal vascular pattern [ 14 , 15 , 16 , 17 ]. Indeed, in the last 20 years, the use of CEUS techniques for the examination of the spleen in humans has been increasingly pursued and several guidelines [ 16 ] and specific studies have arisen [ 16 , 17 ]. However, there are limited studies and reference guides to describe the use of this method for characterizing splenic lesions in veterinary practice.…”
Section: Introductionmentioning
confidence: 99%